Patient‐derived renal cell carcinoma organoids for personalized cancer therapy. Issue 7 (8th July 2022) - Li, Zhichao; Xu, Haibo; Yu, Lei; Wang, Jia; Meng, Qian; Mei, Hongbing; Cai, Zhiming; Chen, Wei; Huang, Weiren
Abstract: Background: Kidney cancer is one of the most common solid tumors. The advancement of human kidney cancer research and treatment has been hindered by a lack of research models that faithfully recapitulate the diversity of the disease. Methods: We established an effective three‐dimensional culture system for generating kidney cancer organoids from clinical renal cell carcinoma samples. Renal cell carcinoma (RCC) organoids were characterized by H&E staining, immunofluorescence, whole‐exome sequencing, RNA sequencing and single‐cell RNA sequencing. The use of RCC organoids in personalized cancer therapy was assessed by testing their responses to treatment drugs and chimeric antigen receptor T cells. Results: Using this organoid culture system, 33 kidney cancer organoid lines from common kidney cancer subtypes, including clear cell renal cell carcinoma (ccRCC), papillary renal cell carcinoma (pRCC), and chromophobe renal cell carcinoma (chRCC), were generated. RCC organoids preserved the histological architectures, mutational landscapes, and transcriptional profile of the parental tumor tissues. Single‐cell RNA‐sequencing revealed inter‐ and intra‐tumoral heterogeneity in RCC organoids. RCC organoids allowed for in vitro drug screening and provided a tool for assessing the efficacy of chimeric antigen receptor T cells. Conclusions: Patient‐derived RCC organoids are valuable pre‐clinical models for academic research and personalized medicine. Abstract : A biobank of patient‐derived renal cell carcinoma organoids was established using a modified culture system. RCC organoids maintain cellular heterogeneity, histological, genomic and transcriptomic characteristics of parental tumours. RCC organoids allow drug testing and can be used in assessing responses to CAR‐T therapies.